Female-Male and Female-Female Social Interactions of Captive Kept Capercaillie (Tetrao Urogallus) and Its Consequences in Planning Breeding Programs - Joanna Rosenberger; Artur Kowalczyk; Ewa Łukaszewicz; Tomasz Strzała (Animals, 2020)
Capercaillie behavior, both in the wild and in captivity, is poorly known due to this species’ secretive way of life. Female-male and female–female social organization and interactions are especially poorly documented. The research was conducted in Capercaillie Breeding Center in Wisła Forestry District where a breeding flock is kept throughout the year. Thanks to video monitoring, we were able to observe mate choice, and then later, female–female interactions during laying and incubation period. Male individual variation in tooting latency and duration were recorded. Females’ interest in males was related to males’ tooting activity, but when males became too insistent and started to chase the females, the females avoided contact with them. There was a significant relationship between calendar date and when tooting starts, and between the tooting duration the female spent with a male. Two incidents of female-male aggression caused by competition for food were observed. Female intruder presence and competition for nesting place was observed in 66.67% nests. Most female–female interactions were limited to threat posturing, but fights and attempts to push out the intruder from the nest occurred as well. Such interactions may lead to nest abandonment and egg destruction, lowering the breeding success.